2017
DOI: 10.1007/s00432-017-2401-y
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study comparing the outcomes and toxicities of intensity-modulated radiotherapy versus two-dimensional conventional radiotherapy for the treatment of children and adolescent nasopharyngeal carcinoma

Abstract: PurposeTo compare the clinical outcomes and toxicities of two-dimensional conventional radiotherapy (2D-CRT) and intensity-modulated radiotherapy (IMRT) for the treatment of children and adolescent nasopharyngeal carcinoma (NPC).MethodsA total of 176 children with non-metastatic NPC treated at Sun Yat-sen University Cancer Center between October 2003 and September 2013 were included in this study. Of the 176 patients, 74 received 2D-CRT and 102 were treated with IMRT. The clinical outcomes and acute and late t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 34 publications
3
66
0
Order By: Relevance
“…In young patients, the predominant histology of NPC is an undifferentiated variant of disease (27)(28)(29), which was confirmed in our study where 98.0% of pediatric patients were histologically WHO type III. On the other hand, ∼96.0% of our patients presented in advanced clinical stage III or IV, similar to other reports with stage III-IV patients accounting for 92.0-97.3% (5,7,29).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In young patients, the predominant histology of NPC is an undifferentiated variant of disease (27)(28)(29), which was confirmed in our study where 98.0% of pediatric patients were histologically WHO type III. On the other hand, ∼96.0% of our patients presented in advanced clinical stage III or IV, similar to other reports with stage III-IV patients accounting for 92.0-97.3% (5,7,29).…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, IMRT has provided excellent locoregional control in children and adolescent NPC patients with LRRFS of 95.2%. Nevertheless, the NPC failure pattern was not altered by IMRT, and distant metastasis remained the major pattern of failure, a result similar to the findings of other reports (5,35,36). We observed that a level of pretreatment EBV DNA >40,000 copies/mL was highly statistically significantly associated with the poorer DMFS and DFS.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Intensity-modulated radiation therapy (IMRT) was a milestone development in RT technology, as IMRT can provide a high conformal radiation dose to the tumor target area while effectively decreasing the dose to the sur-rounding normal tissues. IMRT, instead of 2-dimensional RT (2-DRT) and 3-dimensional conformal RT (3-DCRT), is currently more commonly used to treat NPC, due to the associated better tumor control and lower RT-related toxicities [1][2][3][4][5]. The 5-year overall survival (OS), 5-year local relapse-free survival (LRFS), 5-year regional relapse-free survival (RRFS), and 5-year distant metastasis-free survival (DMFS) rates of patients with NPC treated with IMRT ranged from 74% to 84%, 83% to 95%, 91% to 97%, and 83.3% to 85.6%, respectively [6][7][8][9][10].Both loco-regional relapse and distant metastasis are the main reasons of treatment failure in patients with NPC [6-10].…”
mentioning
confidence: 99%